Miwah Prospect High Sulphidation Au-Cu Mineralisation, Northern Sumatra, Indonesia (4b0407ac-b0c0-4d41-9954-f2633d517077) - Fleming GJ (The Australasian Institute of Mining and Metallurgy, 1995)
The Miwah prospect lies on the dilational 070¦ trending Miwah Lineament near its intersection with northerly oriented fractures within Pliocene volcanic rocks exposed between a NW trending segment of the dextral transcurrent Sumatra Fault, and the more northerly trending Samalanga-Sipopok Fault to the east. These faults reflect the continued interaction between stresses from the India-Australia plate located to the southwest, and spreading within the Andaman Sea to the north of Sumatra. A system of deep seated faults is believed to have facilitated emplacement of post-Miocene magmas and Quaternary volcanic centres at shallow crustal levels throughout northern Sumatra.